Buckling analysis of functionally graded circular plates made of saturated porous materials based on higher order shear deformation theory. (February 2016) - Mojahedin, A.; Jabbari, M.; Khorshidvand, A.R.; Eslami, M.R.
Abstract: This study presents the buckling analysis of radially loaded solid circular plate made of porous material. Properties of the porous plate, where pores are assumed to be saturated with fluid, vary across its thickness. The boundary condition of the plate is assumed to be clamped and the plate is assumed to be geometrically perfect. The higher order shear deformation plate theory (HSDT) is employed to derive the governing equations. The equilibrium and stability equations, derived through the variational formulation and based on the Sanders non-linear strain–displacement relation, are used to determine the prebuckling forces and critical buckling loads. The results are compared with the buckling loads of circular plates made of porous material and reported in the literature based on the classical plate theory (CPT) and the first order shear deformation plate theory (FSDT). Abstract : Highlights: We analyze the buckling of functionally graded circular plates made of porous material on higher order shear deformation theory. The porous plate is assumed of the form that pores are saturated with fluid. And the pores distribution of the plate is variable in the thickness direction and the plate is investigated in three situations. Equilibrium and stability equations of a porous circular plate under radially compressive load are derived. The effects of porous plate, thickness, pores distribution and variation of porosity on the critical mechanical load are investigated.